2013
DOI: 10.1111/avj.12061
|View full text |Cite
|
Sign up to set email alerts
|

Indications, durations and outcomes of mechanical ventilation in dogs and cats with tick paralysis caused byIxodes holocyclus: 61 cases (2008–2011)

Abstract: Dogs and cats with tick paralysis requiring mechanical ventilation to manage respiratory failure have reasonable survival probability. Dogs and cats requiring mechanical ventilation because of hypoventilation have a higher survival probability than those with oxygenation failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 23 publications
(68 reference statements)
3
50
1
Order By: Relevance
“…In these, if respiratory depression is observed, arterial blood gas analyses should be performed to assess oxygenation and ventilation status. 75 Electrophysiological studies in children with tick paralysis demonstrate a severe reduction in the size of the CMAPs, without evidence of denervation potentials on EMG. Increases in amplitude of the CMAPs might be observed in many patients by cooling the limb tested.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In these, if respiratory depression is observed, arterial blood gas analyses should be performed to assess oxygenation and ventilation status. 75 Electrophysiological studies in children with tick paralysis demonstrate a severe reduction in the size of the CMAPs, without evidence of denervation potentials on EMG. Increases in amplitude of the CMAPs might be observed in many patients by cooling the limb tested.…”
Section: Diagnosismentioning
confidence: 99%
“…Although rare in North American cases, Australian dogs and cats with tick paralysis may need mechanical ventilation for survival. 71,75 Tick paralysis in North America is a disease with a good prognosis after the removal of the offending tick. In Australia, tick paralysis is a potentially fatal disease with an estimated mortality rate of 5% despite treatment.…”
Section: Acute Lower Motor Neuron Tetraparesismentioning
confidence: 99%
“…Mechanical ventilation should improve the survival of patients severely affected by tick paralysis, given that respiratory failure is held to be the major cause of death . A recent retrospective study of 61 tick paralysis patients requiring mechanical ventilation reported a survival probability of 90% when they were ventilated because of hypercapnia and 53% when ventilated because of hypoxaemia unresponsive to oxygen therapy . Veterinary and human studies have consistently shown that the prognosis for patients requiring mechanical ventilation for hypercapnic neuromuscular failure is better than for those with hypoxaemic pulmonary disease .…”
Section: Respiratory Support Strategymentioning
confidence: 99%
“…The third small animal paper shows that two-thirds of dogs and cats with respiratory failure induced by the paralysis tick (Ixodes holocyclus) and requiring mechanical ventilation survived to discharge from the hospital. 4 Patients were ventilated because of hypoxaemia refractory to oxygen therapy, hypoventilation, unsustainable respiratory effort or because of respiratory arrest. Those requiring mechanical ventilation because of hypoventilation had a higher survival probability than those with oxygenation failure (91% and 53% respectively).…”
Section: Small Animalsmentioning
confidence: 99%